Etiology of single-sided deafness and asymmetrical hearing loss. (10th March 2017) - Usami, Shin-ichi; Kitoh, Ryosuke; Moteki, Hideaki; Nishio, Shin-ya; Kitano, Tomohiro; Kobayashi, Masafumi; Shinagawa, Jun; Yokota, Yoh; Sugiyama, Kenjiro; Watanabe, Kizuki
Abstract: Conclusions: The present study revealed that various etiologies are involved in single-sided deafness (SSD), and that the cause of SSD and asymmetrical hearing loss (AHL) differed greatly between congenital/early-onset cases and adult cases. Clarification of the etiology is the first step toward providing appropriate intervention. Objectives: The study aimed to clarify the etiology of SSD and AHL patients. Methods: The etiology of a total of 527 SSD or AHL patients who visited Shinshu University Hospital between 2006 and 2016 were analyzed by imaging as well as serological tests for mumps virus, and CMV DNA testing. Results: In our cohort of congenital/early-onset SSD ( n  = 210), the most prevalent cause in children was cochlear nerve deficiency (43.7%; 87 of 199 patients undergoing CT and/or MRI), followed by CMV infection, mumps infection, anomalies of the inner ear, ANSD, and other rare etiologies. In contrast, half of the adult SSD patients presented with idiopathic sensorineural hearing loss, followed by various types of otitis media, cerebellopontine angle tumor and other rare etiologies.